Dissolved and colloidal phosphorus fluxes in forest ecosystems—an almost blind spot in ecosystem research1. Issue 4 (23rd June 2016) - Bol, Roland; Julich, Dorit; Brödlin, Dominik; Siemens, Jan; Kaiser, Klaus; Dippold, Michaela Anna; Spielvogel, Sandra; Zilla, Thomas; Mewes, Daniela; von Blanckenburg, Friedhelm; Puhlmann, Heike; Holzmann, Stefan; et al.
Abstract: Understanding and quantification of phosphorus (P) fluxes are key requirements for predictions of future forest ecosystems changes as well as for transferring lessons learned from natural ecosystems to croplands and plantations. This review summarizes and evaluates the recent knowledge on mechanisms, magnitude, and relevance by which dissolved and colloidal inorganic and organic P forms can be translocated within or exported from forest ecosystems. Attention is paid to hydrological pathways of P losses at the soil profile and landscape scales, and the subsequent influence of P on aquatic ecosystems. New (unpublished) data from the German Priority Program 1685 " Ecosystem Nutrition: Forest Strategies for limited Phosphorus Resources " were added to provide up‐to‐date flux‐based information. Nitrogen (N) additions increase the release of water‐transportable P forms. Most P found in percolates and pore waters belongs to the so‐called dissolved organic P (DOP) fractions, rich in orthophosphate‐monoesters and also containing some orthophosphate‐diesters. Total solution P concentrations range from ca. 1 to 400 µg P L −1, with large variations among forest stands. Recent sophisticated analyses revealed that large portions of the DOP in forest stream water can comprise natural nanoparticles and fine colloids which under extreme conditions may account for 40–100% of the P losses. Their translocation within preferential flow passes may be rapid, mediated by storm events. The potential total P loss through leaching into subsoils and with streams was found to be less than 50 mg P m −2 a −1, suggesting effects on ecosystems at centennial to millennium scale. All current data are based on selected snapshots only. Quantitative measurements of P fluxes in temperate forest systems are nearly absent in the literature, probably due to main research focus on the C and N cycles. Therefore, we lack complete ecosystem‐based assessments of dissolved and colloidal P fluxes within and from temperate forest systems.